Strategy For Organizing An Excellent School In Yogyakarta City - Choirun Nisa' (Nur Science Institute, 2021)
Background: The objective of this study was to analyze the implementation of social attitudes consist of honesty, discipline, responsibility, and tolerance in the elementary schools of Karanganyar Regency, Indonesia. Method: The research method used is a qualitative method, with a phenomenological approach. The research sites are Primary Primary School, SD Muhammadiyah Sokonandi, SD Negeri Ungaran, and SD Tumbuh 2. Research informants are principals, teachers, employees, and school committees—data collection techniques by observation, interviews, and documentation. The qualitative data analysis technique used the Miles and Huberman model. They are testing the validity of the data with extended observations and triangulation. Result: The study results found that: 1) the three elementary schools used different strategies, SD Muh Sokonandi with Ormas and kinship, Ungaran 1 State Elementary School with the Government, and Growing 2 Elementary School with the YEAN Foundation in collaboration with Cambridge. 2) Besides the differences in school strategies, they also have similarities in the use of Website technology as a promotional medium. 3) The three Excellent Elementary Schools with A accreditation, academic achievements, and extracurricular activities are exemplary. SD Muh Sokonandi has school excellence, the number of students, and the moral education of students. SD Negeri Ungaran 1, has the advantage, as a school coach, having the right to conduct elementary school development. Meanwhile, SD Tumbuh 2 has the advantage of the Art-Culture Museum program and collaboration with Cambridge International Primary Program (CIPP), England. Also, the use of Website technology as a promotional medium has similarities. 3) The three primary schools are excellent, with A accreditation, exemplary academic achievements and extracurricular activities. SD Muh Sokonandi has school excellence, the number of students, and the moral education of students. SD Negeri Ungaran 1 has the advantage, as a school coach, having the right to conduct elementary school development. Meanwhile, SD Tumbuh 2 has the advantage of the Art-Culture Museum program and collaboration with Cambridge International Primary Program (CIPP), England. Also have similarities in the use of Website technology as a promotional medium. 3) The three primary schools are excellent, with A accreditation, exemplary academic achievements and extracurricular activities. SD Muh Sokonandi has school excellence, the number of students and the moral education of students. SD Negeri Ungaran 1, has the advantage, as a school coach, having the right to conduct elementary school development. Meanwhile, SD Tumbuh 2 has the advantage of the Art-Culture Museum program and collaboration with Cambridge International Primary Program (CIPP), England. Novelty: The present study revealed the Strategy for Organizing an Excellent Schools